Autodesk Inventor 2013 - Hansen, L. Scott (McGraw-Hill, 2013)
This innovative new Autodesk Inventor 2013 book focuses on teaching people mastery of Autodesk Inventor 2013 with a 'Learn by Doing' pedagogical framework.